2013
DOI: 10.1142/9789814390125_0017
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of the Patterns of International Trade

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 12 publications
5
67
1
1
Order By: Relevance
“…The figures show an orderly development, as is also observed in other multiple 18 Recall that the initial tax rates in the STLS-system are determined by using the outcomes of the constant tax regime of the WT-system. This general impression is confirmed by a convergence analysis based on the following estimation model (see Noussair, Plott, and Riezman (1995)):…”
Section: Constant Tax Regimementioning
confidence: 65%
“…The figures show an orderly development, as is also observed in other multiple 18 Recall that the initial tax rates in the STLS-system are determined by using the outcomes of the constant tax regime of the WT-system. This general impression is confirmed by a convergence analysis based on the following estimation model (see Noussair, Plott, and Riezman (1995)):…”
Section: Constant Tax Regimementioning
confidence: 65%
“…While the costs of produced output are still sunk in this setting, production can adjust upwards in response to current market period conditions. This seems to allow for full equilibration in simple one output good economies (Goodfellow and Plott, 1990;Bosch-Domènech and Silvestre, 1997) and movement towards equilibrium in complex economies with multiple input and output goods (Noussair et al, 1995(Noussair et al, , 1997(Noussair et al, , 2007. However, in all of these cases convergence still occurs from too little production and the ratio of input to output prices from below the equilibrium ratio.…”
mentioning
confidence: 99%
“…Result 10 In an earlier work (Noussair et al 1995), we demonstrated that the patterns of production and trade predicted by the law of comparative advantage are observed in an experimental market. In those markets, members of different countries used the same currency.…”
Section: Resultsmentioning
confidence: 71%